Multimodality Strategy for Cardiovascular Risk Assessment: Performance in 2 Population-Based Cohorts. Issue 22 (30th May 2017) - de Lemos, James A.; Ayers, Colby R.; Levine, Benjamin; deFilippi, Christopher R.; Wang, Thomas J.; Hundley, W. Gregory; Berry, Jarett D.; Seliger, Stephen L.; McGuire, Darren K.; Ouyang, Pamela; Drazner, Mark H.; Budoff, Matthew; et al.
Abstract : Background: Current strategies for cardiovascular disease (CVD) risk assessment among adults without known CVD are limited by suboptimal performance and a narrow focus on only atherosclerotic CVD (ASCVD). We hypothesized that a strategy combining promising biomarkers across multiple different testing modalities would improve global and atherosclerotic CVD risk assessment among individuals without known CVD. Methods: We included participants from MESA (Multi-Ethnic Study of Atherosclerosis) (n=6621) and the Dallas Heart Study (n=2202) who were free from CVD and underwent measurement of left ventricular hypertrophy by ECG, coronary artery calcium, N-terminal pro B-type natriuretic peptide, high-sensitivity cardiac troponin T, and high-sensitivity C-reactive protein. Associations of test results with the global composite CVD outcome (CVD death, myocardial infarction, stroke, coronary or peripheral revascularization, incident heart failure, or atrial fibrillation) and ASCVD (fatal or nonfatal myocardial infarction or stroke) were assessed over >10 years of follow-up. Multivariable analyses for the primary global CVD end point adjusted for traditional risk factors plus statin use and creatinine (base model). Results: Each test result was independently associated with global composite CVD events in MESA after adjustment for the components of the base model and the other test results ( P <0.05 for each). When the 5 tests were added to the base model, the c-statistic improved from 0.74 to 0.79 ( P =0.001), significant integrated discrimination improvement (0.07, 95% confidence interval [CI] 0.06–0.08, P <0.001) and category free net reclassification improvement (0.47; 95% CI, 0.38–0.56; P =0.003) were observed, and the model was well calibrated (χ 2 =12.2, P =0.20). Using a simple integer score counting the number of abnormal tests, compared with those with a score of 0, global CVD risk was increased among participants with a score of 1 (adjusted hazard ratio, 1.9; 95% CI, 1.4–2.6), 2 (hazard ratio, 3.2; 95% CI, 2.3–4.4), 3 (hazard ratio, 4.7; 95% CI, 3.4–6.5), and ≥4 (hazard ratio, 7.5; 95% CI, 5.2–10.6). Findings replicated in the Dallas Health Study were similar for the ASCVD outcome. Conclusions: Among adults without known CVD, a novel multimodality testing strategy using left ventricular hypertrophy by ECG, coronary artery calcium, N-terminal pro B-type natriuretic peptide, high-sensitivity cardiac troponin T, and high-sensitivity C-reactive protein significantly improved global CVD and ASCVD risk assessment. Abstract : Supplemental Digital Content is available in the text.